POST-INDEPENDENCE ENGAGEMENT PARADIGMS IN SELECTED THIRD-GENERATION NIGERIAN NOVELS (2012)
African critical discourse is replete with existing studies on first and second generation novelists and their abiding commitment to socio-historical realities. While the first generation writers focused nationalist ethos, the second generation evinced political activism. However, the third-generation novelists, who exhibit a tendency towards political engagement, have not received adequate critical attention and sufficient comparative evaluation. This study, therefore, examines the engagement paradigms in third-generation Nigerian novels. Psychoanalysis (Freudian and Lacanian) and New Historicism are employed as theoretical frameworks. Psychoanalysis is relevant to the understanding of the internal workings of the human mind at different levels of consciousness which is germane to the characterization in the selected novels for this study. New Historicism entails a dynamic consideration of history and the text from the perspective of both the critic and the writer, which is also central to the selected texts. It involves a close and comparative reading of six purposively selected texts: Chimamanda Adichie's Purple Hibiscus; Sefi Attah's Everything Good Will Come; Okey Ndibe's Arrows of Rain; Adaobi Nwaubani's I Do Not Come To You By Chance; Helon Habila's Waiting for An Angel and Bina Ilagha's Condolences. The novels are content and comparatively analysed along three paradigms of Child Narration, Development Fiction and Quest for Justice. Third-generation Nigerian novelists have upheld and consolidated the tradition of commitment in African literature. The novelists have evolved identified paradigms to engage the post-independence challenges of the enabling milieu. Through the paradigm of Child Narration, ChimamandaAdichie and SefiAttah effectively exploit omniscient narrative technique as a device for projecting socio-historical decadence in Purple Hibiscus and Everything Will Come respectively. Okey Ndibe's Arrows of Rain and Adaobi Nwaubani's I Do Not Come To You By Chance exemplify the appropriateness of the Development Fiction paradigm through the engagement of developmental issues like political corruption, moral decadence and internet fraud prevalent in the twenty-first century. Quest for Justice as an engagement paradigm situates Helon Habila's Waiting for an Angel and BinaIlagha's Condolences as Justice Narratives. It equally manifests in the crusade for prison reforms in Waiting for an Angel and the question of violation of human and communal rights in Condolences. Technically, the paradigms foreground the selected texts by exuding metaphors of neo-colonial decadence, evolution of informed and balanced narrators, narrative devices, suspense and images of socio-historical dislocation. The selected novels share affinities of pragmatic engagement of post-independence decadence and refractive temperament, propelled by the frameworks of the isolated paradigms used in the study. Third-generation Nigerian novels are dynamic and unique in their engagement of post-independence challenges as instantiated in the paradigms of Child Narration, Development Fiction and Quest for Justice. Thus, the refractive capacity of fiction is adequately foregrounded. There is, therefore, an inherent potential of the third-generation Nigerian novel to serve as an imaginative catalyst of socio-political re-engineering.